2016
DOI: 10.1111/1365-2656.12499
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the pace‐of‐life syndrome across species, sexes and individuals: covariation of life history and personality under pesticide exposure

Abstract: The pace-of-life syndrome (POLS) hypothesis integrates covariation of life-history traits along a fast-slow continuum and covariation of behavioural traits along a proactive-reactive personality continuum. Few studies have investigated these predicted life-history/personality associations among species and between sexes. Furthermore, whether and how contaminants interfere with POLS patterns remains unexplored. We tested for covariation patterns in life history and in behaviour, and for life-history/personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 78 publications
(158 reference statements)
4
80
2
Order By: Relevance
“…The parental stress hypothesis proposes that females subjected to low quality food intake produce maladaptive maternal effects in offspring (Rossiter, 1991; Rossiter, 1996; Vijendravarma, Narasimha & Kawecki, 2010) affecting egg quality and/or embryo or larval survivorship. In our case, the preponderance of females in our second generation suggests that male larvae may have been more susceptible to maternal effects due to the differences between sexes in larval activity and/or time needed to emerge (Debecker et al, 2016), or were more susceptible to cannibalism during early larval development (before they were isolated).…”
Section: Discussionmentioning
confidence: 70%
“…The parental stress hypothesis proposes that females subjected to low quality food intake produce maladaptive maternal effects in offspring (Rossiter, 1991; Rossiter, 1996; Vijendravarma, Narasimha & Kawecki, 2010) affecting egg quality and/or embryo or larval survivorship. In our case, the preponderance of females in our second generation suggests that male larvae may have been more susceptible to maternal effects due to the differences between sexes in larval activity and/or time needed to emerge (Debecker et al, 2016), or were more susceptible to cannibalism during early larval development (before they were isolated).…”
Section: Discussionmentioning
confidence: 70%
“…We have previously shown that larval growth rate is well integrated with other life history traits, such as age and size at emergence and adult lifespan, along a fast‐slow life history continuum in I. elegans (Debecker et al. ). We therefore consider growth rate a reliable proxy for pace of life (see also Stamps , Biro and Stamps ).…”
Section: Methodsmentioning
confidence: 99%
“…), only one study investigated how contaminants change covariation patterns between life history and behavior (Debecker et al. ). In the latter study, a positive association between fast life history and risk taking in the presence of predator cues arose only after a pesticide treatment but only in the most fast‐lived species studied.…”
Section: Introductionmentioning
confidence: 99%
“…; Debecker et al . ). Correlations between life history and behaviour are found in many animals (Biro et al .…”
Section: Introductionmentioning
confidence: 97%